(untitled) (Journal of Oriental Studies, 2020)
Islam is a great civilization. The contribution of Islam to the history of mankind is especially significant, since under its banners the flowering of education and science took place, humanity soared to the heights of humanism and sanity. The edges, which turned yellow like a dried up steppe, like a dried riverbed, with the advent of Islam turned into meadows with lush and tall grass. Islam began to penetrate into Central Asia, including in the Kazakh lands in the VIII century AD. In the decisive battle between the Chinese troops of the Tan Dynasty and Muslims on the coast of Talas in 751, the victory of Muslims opened the way to Central Asia not only to Islam, but also to the unhindered spread of its culture. Along with the Holy Quran, Islamic civilization came to the Kazakh lands. Science and education revived. Cities were built. They functioned madrassas and research centers. Deeply thinking scholars came out from among the local people who praised humanism in their works – Abu Nasr al-Farabi, Khoja Ahmet Yasawi, Yusuf Balasaguni, Jamal ad-din Said at-Turkistani, Muhammad Khaidar Dulati, Kadyrgali Jalairi and others. They are proud not only the Kazakh people and Central Asia, but also the entire culture of the Muslim East. Their names are given to streets and avenues, universities and research institutes of Kazakhstan. We are proud of them. The valuable heritage left by great scholars is a treasure trove for us and will always inspire great deeds. Our ancestors left a great spiritual legacy. We must not only master them, but also study and read, because Islam is an indestructible part and support of culture and literature, art and moral values of the Kazakh people. Without the traditions of Islam, it is difficult to imagine the Kazakh culture. Islam was at different times and will be the main pillar of our spiritual development. Many different cultural, scientific and spiritual centers functioned on Kazakh soil – Otrar, Sutkent, Turkestan, Syganak, Barshynkent, Kipchak, Arkok, Zhend, Isfijab-Sayram, Taraz, Balasagun. If we talk about only one Otrar, then we can say that he gave the world Abu Nasra al-Farabi and other gifted scientists, who each made their own contribution to world culture. The vast majority of people know one great scientist – Abu Nasra al-Farabi (870-950). Did Otrar give the world only one Abu Nasr? Our studies show that more than 30 scientists, representatives of various branches of science, education, culture and religion were born and raised in only one Otrar. If information about the life and works of some of them has reached our time, then we know only about grains about others. However, they are very expensive for us. The article highlights the life and creative heritage of a medieval thinker, scientific teacher, Islamic scholar, a native of the city of Zernuzh (Zernuk) – [Burkhan ad-din] al-Numan bin Ibrahim bin Khalil Taj ad-din al-Zernuji (1206), author of the religious-pedagogical Arabic-language work “Talim al-mutaallim tarik al-ulum”. He was born in the city of Zernuj (Zernuk) (Farabsky Vilayat), on the banks of the Saykhun River (Syr-Darya) in the middle of the XI century and died in 1206. Until recently, his work as a textbook was used in various madrassas of both the Arab countries and the Ottoman Empire. Key words: Zernuj (Zernuk), Otrar (Farab), Islam, Mavenerennahr, the Holy Quran, ayat, hadith, Taliban, fiqh, Isfijab (Sairam)